Trainee Perspectives on Relational Cultural Therapy and Cultural Competency in Supervision of Trauma Cases. - Gómez, Jennifer M. (Journal of Psychotherapy Integration, 2020)
Supervision is a key part of training in clinical psychology. From my postdoctoral trainee perspective as a Black woman, I reflect on supervision in 1 of my predoctoral practicum at a community clinic where I worked with low-income women with trauma histories. With relational cultural therapy (e.g., Miller, 1976), my clinical supervision was in the feminist multicultural framework (Porter & Vasquez, 1997) and included the complexities of power in the supervisory relationship, openness, collaboration, and critical self-reflection (Arczynski & Morrow, 2017). Moreover, incorporating research perspectives (e.g., betrayal trauma theory, Freyd, 1996; cultural betrayal trauma theory, Gómez, 2018d; microaggressions, Sue, 2010) and cultural competency (Sue, 1978) created a rich learning environment. In this article, I detail 2 case studies to illustrate exchanges in supervision that positively impacted my professional development. In Case Study 1, my supervisor engendered identification of parallel processing through engaging in mutual empathy and relational reconnection regarding racial discrimination from a client. In Case Study 2, my supervisor used a collaborative approach in treatment planning for a Latina client who was in an abusive relationship. Based on these experiences, implications for supervisors include ongoing training in discrimination of diverse minorities and facilitating discussions in supervision about how trainees' and clients' respective societal statuses impact the therapeutic process (e.g., case conceptualizations, treatment planning). Implications for trainees include maintaining a processing journal, in which trainees reflect on their experiences including but not limited to cultural competency to be better prepared to discuss complex issues in supervision.